Knowledge conflicts resolving in the multi-agent decision support system using multi-stage consensus determining - Sobieska-Karpińska, Jadwiga; Hernes, Marcin (Rozwiązywanie konfliktów wiedzy w wieloagentowym systemie wspomagania decyzji z wykorzystaniem wieloetapowego wyznaczania consensusu, 2012)
The present paper describes using a multi-stage consensus algorithm to knowledge conflicts resolving in multi-agent decision support systems. The problem of knowledge conflict between agents, structure of decision, profile and criteria of consensus determining are presented in the first part of the article. Next, a two-stage algorithm of consensus determining is elaborated. This algorithm, among other things, allows shortening the period of time necessary to take a decision and limiting the risk associated with this process as well as it leads to increased effectiveness of decision-making since solutions generated by agents of an inadequate level of knowledge are not taken into account
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 3 (25), s. 182-194
Keywords: multi-agent systems; decision support system; knowledge conflicts; consensus algorithm; systemy wieloagentowe; systemy wspomagania decyzji; konflikty wiedzy; algorytmy wyznaczania consensusu